PENERAPAN PROGRAM SIX-WEEKS DALAM MENINGKATKAN EFEKTIVITAS DAN MUTU PEMBELAJARAN DISEKOLAH MADRASAH ALAM YA BUNAYYA MUARA BUNGO - Wiwin Narti; Darajoh, Umi; Nur Azizah, Siti; Chairunnisa; Putri Agustina, Nia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the implementation of the Six Weeks Program in enhancing learning effectiveness and quality at Madrasah Alam Ya Bunayya Muara Bungo. Designed as a holistic orientation for early childhood students, the program focuses on developing learning readiness, self-help skills, independence, and Islamic values. Using a qualitative approach with participatory observation and parental testimonies, findings reveal that the program facilitates positive adaptation among children, teachers, and the school environment. Significant improvements were observed in children's independence, social-emotional competence, discipline, and daily self-regulation. The study concludes that the Six Weeks Program serves as an effective holistic learning model, with active school-family collaboration being essential to its success in fostering character development and educational quality.